2013
DOI: 10.1108/ijmpb-03-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty management of projects from the owners' perspective, with main focus on managing delivered functionality

Abstract: Thesis research report noteUncertainty management of projects from the owners' perspective, with main focus on managing delivered functionality Abstract Purpose This paper reports on the work on a doctoral thesis studying uncertainty management of projects. The thesis was in particular studying uncertainty regarding the functionality that the project should deliver. The research also addresses how the project owner's views and interests are taken care of, and the relation between the project management and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Employee satisfaction is a critical factor that impacts their success as a worker, dramatically benefiting the company. Therefore, employee satisfaction is an important driving force for organisations [28]. WFC occurs when there is a demand for targets assigned in work that makes it difficult to fulfil the desires of family life.…”
Section: Factors Influencing the Work-family Interface (Wfi)mentioning
confidence: 99%
“…Employee satisfaction is a critical factor that impacts their success as a worker, dramatically benefiting the company. Therefore, employee satisfaction is an important driving force for organisations [28]. WFC occurs when there is a demand for targets assigned in work that makes it difficult to fulfil the desires of family life.…”
Section: Factors Influencing the Work-family Interface (Wfi)mentioning
confidence: 99%
“…This results in reporting and documenting low levels of uncertainty for scope management. Scope changes can increase the project's preliminary cost [27][28][29]. Several authors [1,29] have identified scope changes after the financing decision as the main reasons behind cost overrun.…”
Section: Frequently Occurring Uncertaintiesmentioning
confidence: 99%